2018
DOI: 10.1371/journal.pone.0200580
|View full text |Cite
|
Sign up to set email alerts
|

Differences in adiposity and diet quality among individuals with inflammatory bowel disease in Eastern Canada

Abstract: The objective of the current study was to characterize the relationship between diet quality and body composition in participants living with IBD, specifically Crohn’s disease (CD) or ulcerative colitis (UC), in Atlantic Canada. Participants from the Atlantic Partnership for Tomorrow’s Health (PATH) study are residents of one of the four Atlantic Canada provinces. Participants who completed the dietary questionnaire and had body composition measured were included in the study (n = 12,462 without IBD, n = 111 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
3
12
0
2
Order By: Relevance
“…The observed lack of difference in BMI between our study groups corresponds with the results of the study by Back et al [ 30 ], who reported a high prevalence of overweight and obesity in patients with IBD. Similarly, in the study of DeClercq et al [ 31 ], participants with ulcerative colitis were characterized by significantly higher body mass and BMI than the control group. However, such observations may be typical especially in ulcerative colitis and not in Crohn’s disease, because individuals with Crohn’s disease tend to have a lower lean mass than those with ulcerative colitis [ 32 ].…”
Section: Discussionmentioning
confidence: 69%
“…The observed lack of difference in BMI between our study groups corresponds with the results of the study by Back et al [ 30 ], who reported a high prevalence of overweight and obesity in patients with IBD. Similarly, in the study of DeClercq et al [ 31 ], participants with ulcerative colitis were characterized by significantly higher body mass and BMI than the control group. However, such observations may be typical especially in ulcerative colitis and not in Crohn’s disease, because individuals with Crohn’s disease tend to have a lower lean mass than those with ulcerative colitis [ 32 ].…”
Section: Discussionmentioning
confidence: 69%
“…Ge et al [148] demonstrated that apelin significantly ameliorates chronic colitis in IL-10 −/− mice, as demonstrated by the decreased disease activity index and inflammatory scores. In IL-10 −/− mice with spontaneous colitis, the administration of a new adipokine, metrnl, decreased pathological alterations in mWAT, increased adipocyte size and ameliorated inflammation [164].…”
Section: Year Study Type Conclusionmentioning
confidence: 97%
“…Epidemiological studies suggest that both the development of obesity and IBD could generate a proinflammatory state through the expression and release of inflammatory cytokines and chemokines in response to the so-called Western diet [164,165]. A Japanese study investigated a possible link between the transition from a traditional diet to a high-fat Western diet, and increased incidence of CD [166].…”
Section: Dietary Links With Ibdmentioning
confidence: 99%
“…23 Crohn hastaları, sıklıkla anormal mezenterik adipoz dokuya sahiptir ve mezenterik yağın, proinflamatuar sitokinlerin bir kaynağı olduğu bulunmuştur. 24 Çalışmalarda, kontrol grubuna kıyasla Crohn hastalarında daha yüksek intra-abdominal/total abdominal yağ oranı ve viseral yağ dokusu alanı olduğu bulunmuştur. 25,26 Bağırsak etrafındaki bu aşırı yağ dokusu, sitokinlerin ve adipokinlerin salgılanması ile proinflamatuar bir ortama katkıda bulunur.…”
Section: Crohn Hastaliği Patofi̇zyoloji̇si̇unclassified
“…25,26 Bağırsak etrafındaki bu aşırı yağ dokusu, sitokinlerin ve adipokinlerin salgılanması ile proinflamatuar bir ortama katkıda bulunur. 24 İBH olan hastalarda, sıklıkla bağırsak mikrobiyotanın çeşitliliğinde azalma ile sonuçlanan bir disbiosis vardır. 27 Crohn hastalarında özellikle Proteobacteria ve Bifidobacteria gruplarının azaldığı, Firmicutes'in arttığı görülmektedir.…”
Section: Crohn Hastaliği Patofi̇zyoloji̇si̇unclassified